2018
DOI: 10.36689/uhk/hed/2018-01-051
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Poverty and Motivation of Workers to Labour in the Field of Agriculture as Effects of Stagnant Economy

Abstract: The aim of the present article is to reveal the consequences of the stagnant economy in Russia. The key problems here are: the high level of taxation, the presence of complex bureaucratic procedures, corruption, the underdevelopment of the regulatory and legal mechanism, the existence of a significant proportion of people with unofficial employment and hidden incomes, as well as a high burden on social infrastructure, financed by federal and regional budgets. The paper found that the most low-paid sectors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Nassif et al (2020) in an article identified that overall economic stagnation in Brazilian economy are caused by misleading economic policies and depressed labour productivity. The agricultural stagnation is said to be the outcome of poverty and lack of motivation to workers in the agriculture sector and even the disparity of prices between agricultural and industrial products (Kuznetsova et al, 2018). Wiesmeier et al (2015), in the study of Central and Northern Europe have concluded that the agricultural stagnation is largely caused by the agricultural mismanagement and climate change mainly since 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Nassif et al (2020) in an article identified that overall economic stagnation in Brazilian economy are caused by misleading economic policies and depressed labour productivity. The agricultural stagnation is said to be the outcome of poverty and lack of motivation to workers in the agriculture sector and even the disparity of prices between agricultural and industrial products (Kuznetsova et al, 2018). Wiesmeier et al (2015), in the study of Central and Northern Europe have concluded that the agricultural stagnation is largely caused by the agricultural mismanagement and climate change mainly since 1990.…”
Section: Introductionmentioning
confidence: 99%
“…For the development of agriculture in Russia was devoted to the works of numerous Russian scientists, including our earlier works (Kuznetsova A.R. et al [3,10,13,14]). Thus, scientists in different parts of the world solve the problems of livestock development, seeking the most rational technologies.…”
Section: Introductionmentioning
confidence: 99%